Implementation of Walking Assisting Equipment and Physical Exercise to Increase Muscle Strength and Improve Physical Mobility in Stroke Patients - Nisa’wahyuningtyas, Karimatun; Iqomh, Muhammad Khabib Burhanuddin (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Stroke is a disease that can occur when some brain cells die due to abnormal blood flow due to blockage or rupture of blood vessels in the brain. This research method is the answer to the report, this research case study uses a nursing process approach which consists of 5 stages, namely assessment, nursing diagnosis, nursing intervention, nursing implementation, and evaluation. Objective: to find out the provision of walking aids and physical exercise in increasing muscle strength and mobility, after being carried out for 3 days on Mr.Y.